2011
DOI: 10.1172/jci41681
|View full text |Cite
|
Sign up to set email alerts
|

LXRβ is required for glucocorticoid-induced hyperglycemia and hepatosteatosis in mice

Abstract: Although widely prescribed for their potent antiinflammatory actions, glucocorticoid drugs (e.g., dexamethasone) cause undesirable side effects that are features of the metabolic syndrome, including hyperglycemia, fatty liver, insulin resistance, and type II diabetes. Liver x receptors (LXRs) are nuclear receptors that respond to cholesterol metabolites and regulate the expression of a subset of glucocorticoid target genes. Here, we show LXRβ is required to mediate many of the negative side effects of glucocor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
76
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 82 publications
(84 reference statements)
6
76
0
1
Order By: Relevance
“…In Vivo Dex Treatment-Female 8-week-old mice were intraperitoneally injected with Dex (1 mg/kg body weight/daily, 5 days) (41). The symptoms of hepatic steatosis and the levels of immune cells were analyzed on day 6.…”
Section: Methodsmentioning
confidence: 99%
“…In Vivo Dex Treatment-Female 8-week-old mice were intraperitoneally injected with Dex (1 mg/kg body weight/daily, 5 days) (41). The symptoms of hepatic steatosis and the levels of immune cells were analyzed on day 6.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid the confounding effects of insulin on lipogenesis, we explored the role of LXR in insulinopenic models of DN induced by streptozotocin (STZ). For the first animal model, based on Lxrα/β −/− mice with STZinduced diabetes, we used male Lxrα/β −/− and matching wild-type mice (C57Bl/6:129SvEv) [30], which were maintained on chow (2016 Teklad Global rodent diet; Harlan Teklad, Mississauga, ON, Canada). At 8 weeks, mice were given daily i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Kidney lipid analysis Tissues were digested in chloroform : methanol (2:1) with a 20:1 volume to tissue ratio, and processed as described previously [30].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some of these GC target genes are regulated ubiquitously, others appear to be cell-type selective, suggesting cooperation between GR and tissue-specific factors or cofactors (17). Indeed, it has been shown that transcriptional regulators such as liver X-receptor β (LXRβ) can contribute specifically to hyperglycemia, hyperinsulinemia, and hepatic steatosis but not to the immunological system responses elicited by GC (18) and that Kruppel-like factor 15 (KLF15) selectively prevents GC-induced muscle atrophy (19). Although it has been shown that GR regulates adipocyte metabolism (12) and that GCs affect adiposity and energy expenditure both centrally (20)(21)(22) and peripherally, the detailed mechanisms underlying these metabolic changes are incompletely understood.…”
mentioning
confidence: 99%